EFEKTIVITAS PENYELENGGARAAN KEPROTOKOLAN DI PEMERINTAH PROVINSI JAWA BARAT: - Adinda Syaila Ramadhanty; Ivan Darmawan; Jovanscha Qisty Adinda (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
The implementation of protocol is a fundamental element in maintaining the image and authority of leaders and the organization itself. Although the 2023 Government Agency Performance Report (LKIP) shows excellent satisfaction with protocol services, the facts on the ground indicate operational inefficiencies in the form of technical communication barriers, workload imbalances, and high dependence on tacit knowledge. This study aims to analyze the level of effectiveness, identify determining factors, and assess the improvement strategies that have been implemented by the protocol department at the West Java Provincial Secretariat Leadership Administration Bureau. This study uses a qualitative method with an evaluative approach, as well as Richard M. Steers' theory of organizational effectiveness, which covers four aspects, namely Goal Attainment, Internal Process, Employee Satisfaction, and Organizational Flexibility. The results show that the effectiveness of the protocol is asymmetrical. Protocol proved to be highly effective in terms of goal attainment and organizational flexibility due to motivating factors, as evidenced by the 90% success rate of core events and the ability to meet objectives. However, there were inhibiting factors that resulted in moderate effectiveness in terms of internal processes and employee satisfaction due to communication bottlenecks and deviations in logistical support aspects of up to 60%. This system serves to digitize protocol work systems through Digital Pocket Books, secure tactical command channels, and ensure data-based performance accountability.